Current Understanding on Perioperative Management in Lung Cancer: Implications for Anesthetic Considerations - Wang J; Liu L; Song Y; Jiao J; Zhong Y (Dove Medical Press, 2021)
Jian Wang,1 Lei Liu,2 Yuli Song,3 Jinghua Jiao,4 Yifan Zhong2 1Department of Anesthesiology, First Hospital of China Medical University, Shenyang, Liaoning, 110001, People’s Republic of China; 2Department of Ophthalmology, First Hospital of China Medical University, Shenyang, Liaoning, 110001, People’s Republic of China; 3Department of Gynaecology, The First Affiliated Hospital of China Medical University, Shenyang, Liaoning, 110001, People’s Republic of China; 4Department of Anesthesiology, Central Hospital, Shenyang Medical College, Shenyang, 110024, People’s Republic of ChinaCorrespondence: Jinghua JiaoDepartment of Anesthesiology, Central Hospital, Shenyang Medical College, Shenyang, 110024, People’s Republic of ChinaEmail jean0905@163.comYifan ZhongDepartment of Ophthalmology, First Hospital of China Medical University, Shenyang, Liaoning, 110001, People’s Republic of ChinaEmail zhongyifan851111@163.comAbstract: Narcotic drugs are often used to treat perioperative pain for patients with lung cancer. However, anesthetic management and narcotic substance use may have significant impacts on patients with lung cancer, including anti-cancer or promoting cancer effects. In this study, we summarize the effects of anesthetic management and its related substances on lung cancer. An evidence-based review of the influence of anesthetic techniques and narcotic substances used on lung cancer was performed. The effects of perioperative pain management and the method of choosing anesthesia for patients with lung cancer were explored. Different management techniques of anesthesia have been indicated to suppress both cell-mediated immunity and humoral immunity and have effects on the recurrence and metastasis of lung cancer. Evidence suggests that the effects of narcotic substances used on lung cancer were still inconsistent. However, the mechanisms by which anesthetics and analgesics inhibit the tumor are complicated. Perioperative management leads to decreased immunity in patients with lung cancer, which to some extent contributes to recurrence and metastasis. Various narcotic substances used may modulate signal pathways, including the mitochondrial pathway, and appear to exert different effects on the recurrence and metastasis of lung cancer. The anesthesiologists should consider these effects on perioperative management with lung cancer.Keywords: narcotic substance use, anesthetics, lung cancer